2019
DOI: 10.1002/celc.201900553
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of a Conjugated Polydianion‐Based Single‐Ion Conducting Polymer for High‐Performance Solid Lithium‐Ion Batteries

Abstract: Fluorosulfonimide lithium salts have been widely used as conductors in solid polymer electrolytes for solid Li‐ion batteries (LIBs). However, low conductivity and poor compatibility with the polymer host (usually polyethylene oxide, PEO) remain challenges in the design of these salts. In this paper, we synthesized a highly Li+‐conductive salt containing the poly(perfluoroalkylsulfonyl)diimide (PFSDI−) dianion for the first time. LiPFSDI represents the first example of a single Li‐ion‐conducting polymer (SLICP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Polyanions in reports mainly include alkyl carboxylates, [ 108 ] sulfonates, [ 109 ] sulfonylimides, [ 110,111 ] and borates [ 112 ] in view of immobilized anions. Choosing an appropriate polyanion species is vital to the single‐ion conductor design.…”
Section: Macromolecular Design Of Polymer Matrixmentioning
confidence: 99%
“…Polyanions in reports mainly include alkyl carboxylates, [ 108 ] sulfonates, [ 109 ] sulfonylimides, [ 110,111 ] and borates [ 112 ] in view of immobilized anions. Choosing an appropriate polyanion species is vital to the single‐ion conductor design.…”
Section: Macromolecular Design Of Polymer Matrixmentioning
confidence: 99%
“…It was shown that Li dendrite growth could be eliminated with a SIC electrolyte of low mechanical strength . Bis­(trifluoromethyl sulfonyl)­imide (TFSI – )-based polymers have been intensively studied because they display weaker coordination between Li + and the anions compared with other systems, such as those with carboxylate and sulfonate anions. Bouchet et al reported the use of a polystyrene (PS)-PEO block copolymer with TFSI – bonded to PS where the microphase-separated PEO molecules are employed for conducting Li + . A t Li + above 0.85 was achieved with an ionic conductivity of 1.3 × 10 –5 S cm –1 at 60 °C.…”
Section: Introductionmentioning
confidence: 99%